2007
DOI: 10.1007/s12094-007-0080-x
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer and Hedgehog signalling pathway

Abstract: The Hedgehog (Hh) family of intercellular signalling proteins have come to be recognised as key mediators in many fundamental processes in embryonic development. Their activities are central to the growth, patterning and morphogenesis of many different regions within the bodies of vertebrates. In some contexts, Hh signals act as morphogens in the dose-dependent induction of distinct cell fates within a target field, in others as mitogens in the regulation of cell proliferation or as inducing factors controllin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Recently, dysregulated activation of SHH signaling has been observed in small cell lung cancer [12], pancreatic carcinoma [13], prostate cancer [14], and gastric cancer [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, dysregulated activation of SHH signaling has been observed in small cell lung cancer [12], pancreatic carcinoma [13], prostate cancer [14], and gastric cancer [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…They called this cell population cancer stem cells (CSC) [1] . Since then, putative CSC have been isolated from many other tumors including breast, brain, colon, pancreas, prostate, lung and head and neck tumors [2][3][4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced Hedgehog signaling was found to be associated with progression and acceleration of prostate cancer. Recent experiments have shown important role of Hedgehog signaling in prostate cancer, and autocrine Hedgehog signaling by tumor cells is required for proliferation, viability, and invasive behavior of prostate cancer [141]. It has been shown that activation of Hedgehog signaling is involved in CSCs and EMT features in several types of cancers including colon, gastric, esophagus, hepatic, and other cancers [142146].…”
Section: Self-renewal Pathways Of Cancer Stem Cellsmentioning
confidence: 99%